1973
DOI: 10.2307/4594731
|View full text |Cite
|
Sign up to set email alerts
|

Federal Health Services Grants

Abstract: FEDERAL HEALTH SERVICES grants are again in a period of transition. These programs have experienced many changes since they were established on a continuing basis almost 50 years ago by the Social Security Act of 1935. The proposal of President Reagan in February 1981 that most of these activities be consolidated into "block grants" began a new phase of development. The initial action of the Congress on the President's proposal, that was completed in July 1981, indicated a willingness to approve some, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In other words, the likelihood that a low-income woman would receive family planning services became more dependent upon her state of residence than before. Studies of other health programs have suggested that when the level of categorical support (e.g., Title X) decreased, the degree of added state support depended on such factors as the state's previous experience with the program and "the nature of the local constituency" (Zwick, 1986;Bovbjerg & Davis, 1983). Instead of enhancing the responsiveness to local needs, federal grants became more responsive to existing state level constituencies.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the likelihood that a low-income woman would receive family planning services became more dependent upon her state of residence than before. Studies of other health programs have suggested that when the level of categorical support (e.g., Title X) decreased, the degree of added state support depended on such factors as the state's previous experience with the program and "the nature of the local constituency" (Zwick, 1986;Bovbjerg & Davis, 1983). Instead of enhancing the responsiveness to local needs, federal grants became more responsive to existing state level constituencies.…”
Section: Resultsmentioning
confidence: 99%